Distressed personality without a partner enhances the risk of depression in patients with coronary heart disease. (5th December 2012) - Lim, Hong Euy; Lee, Moon‐Soo; Ko, Young‐Hoon; Park, Young‐Min; Han, Changsu; Joe, Sook‐Haeng
Abstract: Introduction: Cultural differences in the combined effects of Type D personality and other mediating factors in the Asian population have not been reported. We examined the influence of the Type D personality in relation to the presence of a partner by measuring symptoms of anxiety and depression, quality of life, self‐perception of health status in coronary heart disease (CHD) patients and normal controls. Methods: Normal controls ( n = 541) and patients with CHD ( n = 110) were included. All participants completed self‐report measures on Type D personality, questionnaires on socio‐demographic factors, the Spielberger State and Trait Anxiety Inventory‐State (STAI‐S), and the Center for Epidemiologic Studies Depression Scale (CES‐D). By stratifying participant group, personality type, and partner status, eight groups were constructed. Results: The subjects with Type D personality showed higher mean scores on the STAI‐S and CES‐D as well as perception of their health. In cases of depression, CHD patients with Type D personality and without partner showed about a 50‐fold increase in odds ratio when compared with non‐Type D normal controls with partners. Odds ratio for depression changed from 31.44 to 48.72 in CHD patients with Type D personality based on the existence of a partner. Discussion: Having a partner significantly predicted the risk of depression. It is important to identify social support systems in CHD patients with Type D personality.